GATA3 Expression in Breast Carcinoma: Associations with Clinicopathological Features - Sriwidyani, Ni Putu; Dewi, I Gusti Ayu Sri Mahendra; Sinaga, Naomi Juliana; Dewi, Ni Putu Wulan Tantri (Indonesian Journal of Cancer, 2024)
Background: Breast carcinoma is a heterogeneous disease, morphologically and molecularly. GATA binding protein 3 (GATA3) is an important marker in breast cancer origin. GATA3 expression and its prognostic value in breast carcinoma are inconsistent. Tumor budding is a small cluster of malignant cells in the invasive edge of the tumor. Breast carcinoma with highgrade tumor budding has an unfavorable prognosis. The objective of this study was to determine whether there is a relationship between GATA3 expression and clinicopathological parameters in breast carcinoma including with tumor budding grade. Another objective of this study was to determine the association between GATA3 expression and other clinicopathological factors with nodal status. Methods: This was a cross-sectional study involving breast carcinoma patients at Prof. Dr. I.G.N.G Ngoerah Hospital during the year 2022 who underwent mastectomy and axillary node dissection. GATA3 expression was determined by immunohistochemistry and categorized into weak and strong expression. Tumor budding was evaluated in Hematoxylin Eosin slides and categorized into low and high grades. The association between GATA3 expressions and clinicopathological parameters, and the association between GATA3 expression and clinicopathological parameters with nodal status, were assessed with a chi-square test with a significance level determined at p 0.05. Results: There were 61 breast carcinoma patients with mastectomy and axillary node dissection that fulfilled inclusion and exclusion criteria. GATA3 expression was significantly associated with the histological type (p = 0.012) and molecular subtype (p 0.001) of the tumor. There was an association between nodal status and molecular subtype of tumor (p = 0.012), tumor stage (p = 0.005), and tumor budding grade (p = 0.024), but there was no association between GATA3 expression and nodal status (p = 0.066). Conclusion: GATA3 expression is associated with the histological type and molecular subtype of tumor in breast carcinoma, but not with nodal status. Nodal status was associated with molecular subtype, T stage, and tumor budding grade of tumor.